2015
DOI: 10.1534/g3.115.020677
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Sequence Analyses of Mitochondrial DNA Insertions in Nuclear Chromosomes of Maize

Abstract: The transfer of mitochondrial DNA (mtDNA) into nuclear genomes is a regularly occurring process that has been observed in many species. Few studies, however, have focused on the variation of nuclear-mtDNA sequences (NUMTs) within a species. This study examined mtDNA insertions within chromosomes of a diverse set of Zea mays ssp. mays (maize) inbred lines by the use of fluorescence in situ hybridization. A relatively large NUMT on the long arm of chromosome 9 (9L) was identified at approximately the same positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…However, XP-CNV analyses are subject to false discovery. First, organelle sequences homologous to nuclear chromosomes could result in high variation in read depths (Lough et al, 2015 ). The number of organelles, such as mitochondria or chloroplasts, varies in different tissues and the percentage of organelle genomes in DNA samples is subject to DNA extraction procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, XP-CNV analyses are subject to false discovery. First, organelle sequences homologous to nuclear chromosomes could result in high variation in read depths (Lough et al, 2015 ). The number of organelles, such as mitochondria or chloroplasts, varies in different tissues and the percentage of organelle genomes in DNA samples is subject to DNA extraction procedures.…”
Section: Discussionmentioning
confidence: 99%
“…NUMT variability is found intraspecifically or even intraindividually as well. Lough et al (2008Lough et al ( , 2015 studied NUMTs in a set of maize inbred lines, showing extensive NUMT variation in size and location among lines, suggesting that mtDNA is being incorporated or lost from the maize nuclear genome continuously. The same is true for cpDNA insertions; Roark et al (2010) studied the NUPTs into maize chromosomes of the same lines.…”
Section: Numts Genes and Pseudogenes Identification And Variabilitymentioning
confidence: 99%
“…Michalovova et al (2013) found mtDNA and cpDNA insertions located at the pericentromeric regions of Arabidopsis and rice. Lough et al (2008Lough et al ( , 2015 studied mtDNA insertions in a set of maize inbred lines and found extensive variation in size and location among lines, but in many lines the signals were located near the centromere or the telomere. Caro et al (2010) using FISH in bone marrow cells of young and old rats reported that 10 pairs of chromosomes showed mtDNA signal located always at the pericentromeric region in rats of both ages.…”
Section: Numts Are Frequently Located At Pericentromeric and (Or) Submentioning
confidence: 99%
“…The ability of doxorubicin to induce DSBs directly due to intercalation into DNA and inhibition of topoisomerase II, and indirectly by the generation of reactive oxygen species has been shown previously [ 17 ]. The successful application of fluorescence in situ hybridization (FISH) for examining the variation in mtDNA insertions in nuclear chromosomes of human [ 8 ], maize [ 18 ], and rat [ 19 ] was the reason for selecting this method in our study.…”
Section: Introductionmentioning
confidence: 99%